The fishes of the families Pomacentridae, Labridae and Callyodontidae, collected by the United States Bureau of Fisheries steamer "Albatross", chiefly in Philippine seas and adjacent waters. - Fowler, Henry W.; Bean, Barton A. (U.S. Govt. print. off., 1928)
At head of title: Contributions to the biology of the Philippine archipelago and adjacent regions